(untitled) (Third Sector Social Economic Review, 2023)
This study aims to examine the differences in the brand values of the companies in 2020 due to the COVID-19 epidemic by measuring the brand values obtained by using the Hirose method of the leading companies in the food and beverage sector listed in Istanbul Stock Exchange. The Hirose method, which is very popular among brand valuation methods, was used in the study. With this method, the prestige values, expansion values and loyalty values of the companies included in the study were measured. After that, the brand values of the companies are calculated as a function of their prestige values, diffusion values, loyalty values and the discount rate of the company used for comparison. Anadolu Efes, Tukaş and Ülker companies were used for comparison and Kerevitaş was used as the benchmark company in the study. Expectedly, the results of the study showed that the brand values of Anadolu Efes, an alcoholic beverage company, suffered a loss in 2020, when the brand values of 2020 were compared with the brand values in 2019 and 2021, while the brand values of Tukaş and Ülker, the food brands, continued to increase despite the pandemic crisis. Findings of the study is in alignment with the literature, confirming that consumers focus on compulsory consumption during crisis periods and reduce non-essential consumption such as alcoholic beverages, but also show that this situation is reflected in the brand values of the companies. Since the COVID-19 epidemic and similar ""black swan"" events are not frequent, there is no similar study known to the author that investigates the effects of consumption behavior differences that may arise in such cases on brand value.